Opportunistic election timing, a complement or substitute for economic manipulation? - Beckman, T; Schleiter, P (University of Chicago Press, 2020)
Parliamentary governments often use their powers opportunistically to enhance their reelection chances. Yet, how they combine the two most commonly available strategies—economic manipulation prior to elections and opportunistic election timing—remains poorly understood. Do incumbents employ these powers jointly, or does the power to time elections temper incentives to engage in distortive economic manipulation? Previous research gives contradictory answers to these questions. We advance the debate by presenting the first cross-national comparative analysis of the effects of opportunistic election timing on economic manipulation, drawing on data from 20 developed parliamentary democracies. Our results demonstrate a powerful substitution effect: when leaders can time elections, they are significantly less likely to manipulate the economy. This finding not only clarifies the theoretical debate, it also has practical implications for political reforms that aim to prevent incumbents from distorting elections in their favor.